AN EVALUATION OF THE EFFECT OF AGGREGATE TYPE ON HOT MIX ASPHALT PROPERTIES IN KURDISTAN REGION OF IRAQ - ALYOUSIFY, SHEYAN; TAHER, SUNDIS M. S. (Journal of Duhok University, 2021)
Hot mix asphalt (HMA) is a mixture that contains, approximately 95% by weight of aggregates. As a consequence the types of aggregates and their characteristics are of most significance in enhancing the durability of asphalt mixture worldwide. Accordingly the impact of aggregate type and gradation has been the focus of many researchers all over the world. In this investigation the effect of aggregate type on HMA in Kurdistan region/ Iraq were spotlighted. More precisely, in addition to gravel which is dominantly used in Kurdistan, crushed stone and limestone were the other types of aggregates that were concerned in the present work. The volumetric properties using Marshall Method of asphalt containing each of these aggregates were inspected. Moreover, the characteristics of aggregates that examined in this study were specific gravity and toughness (Los Angeles abrasion test). Experimental observations revealed that the toughness of gravel and crushed stone was higher than that of limestone as the L.A. abrasion for the latter was considerably higher than that of crushed stone and gravel. Crushed stone with 4.2% binder content resulted in an acceptable flow value according to Iraqi SORB/2003 as well as gravel mix of 4% binder content, while limestone with higher optimum binder content of 6% recorded a non-acceptable value of 4.4 mm. The stability of limestone mix appeared to be higher by 36% and 50% than that for crushed stone and gravel mix, respectively.